The variety of individual attributes as a basis for organisational adaptivity: a case study - Scamans, Jane (Cranfield University, 1997)
A growing literature has emerged which calls for organisations to become more adaptive in the face of complex and uncertain operating environments. This thesis reviews literature dealing with organisational learning and argues that individual attributes are undervalued. There . has been an emphasis on the mechanistic features of the individual within the organisation to the detriment of other attributes such as personal skills and knowledge. A case is made for a more human-centred approach to managing change which focuses upon the exploitation of these particular human factors as one of the central sources of adaptive potential. While some of these factors are formally recognised in the workplace it is argued that many others are acquired outside and therefore do not always appear to have immediate relevance or value. Evidence for this is drawn from a case study in the Commission for Local Administration. This employed a multi-method investigative approach to identify the variety of individual attributes and results are presented in the form of personal process maps which represent individual perceptions of the process of change. These support a broad classification of individual variety to be described. Findings are exploited to both identify the role of individual attributes in managing change and to construct a typology of individual attributes as a basis for adaptive capability. A number of concluding inferences are made regarding implications for management and future work.